Kinetika Fermentasi Selulosa Murni oleh Trichoderma reesei QM 9414 Menjadi Glukosa dan Penerapannya pada Jerami Padi Bebas Lignin - M. Iyan Sofyan (agriTECH, 2004)
The objectives of this research were: 1) to determine aeration rate and substrate concentration of pure cellulose to produce maximum glucose by Trichoderma reesei QM 9414 at 30 Â°C, and agitation at 150 rpm; 2) to study the kinetics of pure cellulose fermentation by Trichoderma reesei QM 9414 to glucose and its implication upon fermentation of the lignin free rice straw. The experiment was arranged in factorial randomized complete design consisted of three levels of aeration (1,00 vvm; 1,5 vvm; 2,0 vvm) and three levels of substrate concentration (0,75 %; 1,00 %; 1,25 % w/v). The results showed that at the exponential phase that the average specific growth of Trichoderma reesei QM 9414 was 0,05374 hour-I, the maximum glucose product concentration of pure cellulose was 0.1644 gri ,and the oxygen transfer was 0,0328 mg L-1 hour-i. According to t-test, the kinetics of pure cellulose fermentation model just the same as the lignin 'free rice straw fermentation. The enzymes produced by Trichoderma reesei QM 9414 in pure cellulose fermentation media followed the Michaelis-Menten model. The enzyme kinetic parameters were the maximum growth Michaelis-Menten constant hour rate was 37x10-3 hour-1 and was 1/2 maximum p 17,5x10.3. The volumetric oxyfen transfer (K,) using rice straw was 0,0337 mg. hour . The value of KIA, could be used for conversion from bioreactor at laboratory scale to commercial scale design.